2019
DOI: 10.1371/journal.pone.0219479
|View full text |Cite
|
Sign up to set email alerts
|

An integrated assessment of nitrogen source, transformation and fate within an intensive dairy system to inform management change

Abstract: From an environmental perspective optimised dairy systems, which follow current regulations, still have low nitrogen (N) use efficiency, high N surplus (kg N ha -1 ) and enable ad-hoc delivery of direct and indirect reactive N losses to water and the atmosphere. The objective of the present study was to divide an intensive dairy farm into N attenuation capacity areas based on this ad-hoc delivery. Historical and current spatial and temporal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…A water-holding capacity around 60% is the threshold for maximum aerobic activity ideal for ammonification and nitrification [63]. Plant-available N can be compared with WFPS, as previous studies have shown a link between WFPS, soil moisture, and N 2 O emission [64][65][66]. Results indicated that inorganic N content was elevated even when WFPS surpassed the 60% threshold at the October 2018 sampling time, although generally, high inorganic N was observed with WFPS at ~60%, ideal conditions for this parameter.…”
Section: Soil Inorganic Nitrogenmentioning
confidence: 99%
“…A water-holding capacity around 60% is the threshold for maximum aerobic activity ideal for ammonification and nitrification [63]. Plant-available N can be compared with WFPS, as previous studies have shown a link between WFPS, soil moisture, and N 2 O emission [64][65][66]. Results indicated that inorganic N content was elevated even when WFPS surpassed the 60% threshold at the October 2018 sampling time, although generally, high inorganic N was observed with WFPS at ~60%, ideal conditions for this parameter.…”
Section: Soil Inorganic Nitrogenmentioning
confidence: 99%
“…There are two cattle underpasses under public roadways and these provide connectivity and delivery of nutrients from underpasses to waters (both surface and groundwater) if tanks are not maintained (Figure 2). A detailed description of the surface and sub-surface drainage system network installed on the farm and its connectivity and impact on a second order stream is available in Clagnan et al (2019) and Ezzati et al (2020).…”
Section: Study Sitementioning
confidence: 99%
“…In terms of N, Fenton et al (2009) proposed a model where nitrate concentration and denitrification rate were correlated with soil and subsoil permeability. Therefore, in terms of water purification heavier textured soils offer more protection but some studies have shown nitrate conversion to ammonium or gaseous phases in both mineral and organic soils (Clagnan et al, 2019). In terms of P, fields with a high soil test P, or high amounts of legacy P pose a greater risk of P loss into a connected hydrological pathway compared to fields that are low or deficient in P (Kurz et al, 2005).…”
Section: Existing Off-roadway Management Options 241 Adjacent Fieldsmentioning
confidence: 99%